Rehabilitation of maxillary bilateral regional odontodysplasia in a 7-year-old child using modified essix retainer - M Divya Banu; V Krishna Priya; Shilpa Gaddam; Santosh Kumar Challa (Wolters Kluwer Medknow Publications, 2022)
Regional odontodysplasia (RO), also called ghost teeth, is a rare nonhereditary developmental dental anomaly affecting the epidermal and mesenchymal tissues associated with the development of tooth which can affect both primary and permanent dentition. It can affect the child's overall quality of life and sometimes may lead to skeletal malocclusion. Management of such patients requires a multidisciplinary approach. Essix retainers are being widely used as retention appliances. Various modifications of this appliance are also being attempted. Thus, this article aims to focus on the use of Essix retainer as an interim prosthesis by modifying it with the incorporation of pontics to manage partial edentulousness and mild orthodontic corrections in a 7-year-old child diagnosed with bilateral RO.